Analysis of Temperature Distribution During Grinding with Variable Wheel Feed - Strelchuk, Roman; Riabenkov, I. (EAI Endorsed Transactions on Digital Transformation of Industrial Processes, 2026)
INTRODUCTION: Creep-feed grinding of ultrahard cutting tool materials such as cermet presents significant thermal challenges due to extended contact arc lengths between wheel and workpiece combined with low thermal conductivity of the workpiece material. These conditions lead to dramatic temperature rises and potential burnout phenomena that compromise grinding quality and wheel life.OBJECTIVES: This study aims to experimentally investigate grinding temperature distribution within the contact arc during creep-feed grinding of cermet workpieces, identify critical burnout conditions, and determine optimal grinding parameters to enhance cooling effectiveness and prevent thermal damage. METHODS: Grinding temperature measurements were conducted using an embedded thermocouple method during creep-feed grinding of Ti(C,N) cermet alloy with hybrid-bonded diamond wheels. Temperature distributions along the contact arc were measured across various combinations of worktable speeds (40–80 mm/min), wheel speeds (14.7–62.9 m/s), and wheel diameters (140 mm and 200 mm). The onset and progression of burnout phenomena were systematically documented and analyzed.RESULTS: Experimental results revealed that burnout occurs when grinding temperature reaches approximately 150°C, causing abrupt temperature increases exceeding 400°C. Burnout initiates at the rear of the contact arc and progressively extends throughout the grinding zone. A critical worktable speed exists above which burnout occurs under constant depth of cut and wheel speed conditions. Smaller wheel diameters and optimized wheel speeds significantly improve cooling effectiveness. At wheel speed of 41.9 m/s, burnout was nearly eliminated with maximum temperatures maintained below 150°C along the entire contact arc, resulting in reduced grinding forces and wheel wear. CONCLUSION: The research demonstrates that strategic control of grinding parameters, particularly wheel speed optimization and wheel diameter selection, effectively prevents burnout and enhances cooling performance in creep-feed grinding of difficult-to-grind cermet materials. Higher wheel speeds improve grinding fluid circulation and cooling effectiveness up to an optimal threshold, beyond which excessive heat generation and reduced fluid supply negate these benefits.
Keywords: grinding temperature distribution; burnout phenomenon; film boiling; cermet machining; creep-feed grinding optimization; hybrid-bonded diamond wheel; thermal management